Optimization of Spinal Anesthesia for Operative Delivery in High-Weight Women - I. P. Zharkov; A. A. Lavrentyev; L. I. Firsova (Общая реаниматология)
Objective: to develop a scheme for calculating the dose of a local anesthetic (LA) for spinal anesthesia (SA) during operative delivery, by taking into account the individual physical characteristics of a female patient. Subjects and methods. The course of SA was analyzed in 35 overweight women. In accordance with the body mass index (BMI), the patients were divided into 3 groups. In each group the authors identified subgroups with no arterial hypotension development (NAHD) and with arterial hypotension development (AHD) until a fetus was extracted. In each specific case, the used dose of a LA was compared with its dose calculated by the height of a patient and the difference between the BMI of a female patient and that taken as the normal value of 25 kg/m2. Results. When the doses of a LA, which were used for SA, were investigated, in all cases the doses of a LA were determined to be smaller than those calculated by the height of a patient. In the NAHD subgroups, the percentage reduction in LA doses was significantly greater than that in the AHD subgroups in all the three groups and the dose was increased as BMI rose from 13.6±1.6% in the NAHD subgroup in Group 1 to 34.7±1.2% in the same subgroup in Group 3. By comparing the percentage reduction in the LA dose and excess BMI, the authors established the correction coefficient for the LA dose calculated by height and derived a formula for calculating the dose of a LA, by taking into account the physical characteristics of a female patient. Conclusion. The LA dose calculation formula considering the individual physical characteristics of a female patient makes the determination of a LA dose more precise in order to optimize the course of anesthesia from the hemodynamic profile. Key words: spinal anesthesia, obesity, cesarean section.